The Science of Well-Being 2005
DOI: 10.1093/acprof:oso/9780198567523.003.0017
|View full text |Cite
|
Sign up to set email alerts
|

* The social context of well-being

Abstract: Large samples of data from the World Values Survey, the US Benchmark Survey and a comparable Canadian survey are used to estimate equations designed to explore the social context of subjective evaluations of well-being, of happiness, and of health. Social capital, as measured by the strength of family, neighbourhood, religious and community ties, is found to support both physical health and subjective well-being.Our new evidence confirms that social capital is strongly linked to subjective well-being through m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

58
641
6
29

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 538 publications
(734 citation statements)
references
References 26 publications
58
641
6
29
Order By: Relevance
“…By contrast to the analysis by Helliwell and Putnam, 7 we did not observe a significant association between the community-level scale that included trust (FSC1_) and health, controlling for individual-level social capital. Additionally, we determined a significant relation between the community-level scale that included formal group involvement (FSC3_) and health.…”
Section: Discussioncontrasting
confidence: 99%
“…By contrast to the analysis by Helliwell and Putnam, 7 we did not observe a significant association between the community-level scale that included trust (FSC1_) and health, controlling for individual-level social capital. Additionally, we determined a significant relation between the community-level scale that included formal group involvement (FSC3_) and health.…”
Section: Discussioncontrasting
confidence: 99%
“…The modern emergence of social capital concept renewed the academic interest for an old debate in social science: the relationship between trust, social networks and the development of modern industrial society. Previous research has indicated that there is an association between social networks and a number of health outcomes [37]- [38]. Granovetter [3] has argued that social relations and the obligations inherent in them are two main sources of trust in economic life.…”
Section: Research's Literaturementioning
confidence: 99%
“…The enhancement of a secure attachment base in older people may assist in moderating agism and improving older people's quality of life (Bodner and Cohen-Fridel 2010). Having a family enhances subjective well-being, and spending more time with one's family helps even more (Helliwell and Putnam 2005). Frequent interactions with both friends and neighbors are associated with systematically higher assessments of subjective well-being (Helliwell and Putnam 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Having a family enhances subjective well-being, and spending more time with one's family helps even more (Helliwell and Putnam 2005). Frequent interactions with both friends and neighbors are associated with systematically higher assessments of subjective well-being (Helliwell and Putnam 2005). Therefore, the social protection systems based on the priority of males' employment under the Conservative model to some extent might exert negative influence on the functions and roles of males in the family and social life, which may be associated with relatively high suicide rates among older males in these Continental countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation